Giant congenital melanocytic nevi: 40 years of experience with the serial excision technique - Lais de Abreu Mutti; Marta Regina Machado Mascarenhas; João Marcos Goes de Paiva; Ronaldo Golcman; Mauro Yoshiaki Enokihara; Benjamin Golcman (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Although giant congenital melanocytic nevus is a rare lesion, it causes significant deformity and carries a risk of malignant degeneration. Different surgical techniques for the lesion removal are described, including serial resection, resection with skin grafting, and resection and coverage with expanded skin flap (skin expanders). The aim of this study is to report the author's 40 years of experience with cases requiring at least 4 serial excisions to complete the treatment. Serial resection is an effective, safe, and simple technique that requires a lot of patience. Treatment often results in a single linear scar, requires no donor sites, nor large flaps. It is not subject to potencial complications of expanders and avoid aesthetic deformities depending on the location.